Performance Research on IEEE 802.11a 54 Mbps WPA2 Laboratory Links - Carvalho, José Pacheco de (2019)
The increasing importance of wireless communications, involving electronic devices, has been widely recognized. Performance is a fundamental issue, resulting in more reliable and efficient communications. Security is also crucially important. Laboratory measurements are presented about several performance aspects of Wi-Fi IEEE 802.11a 54 Mbps WPA2 point-to-point and point-to-multipoint links. Our study contributes to performance evaluation of this technology under WPA2 encryption, using available equipments (HP V-M200 access points and Linksys WPC600N adapters). New results are given from TCP and UDP experiments concerning TCP throughput versus TCP packet length, jitter and percentage datagram loss versus UDP datagram size. Comparisons are made to corresponding results for Open links. Conclusions are drawn about the comparative performance of the links.